New records of protected, threatened, and rare vascular plant species in the Lower Bug Valley (eastern Poland) - Szulc, Adam Piotr; Wiśniewski, Marcin (Biodiversity: Research and Conservation, 2024)
We present new localities and verified published records of protected, rare, and threatened vascular plant species in the Mazovia region, mostly in the left-bank part of the Lower Bug Valley (Dolina Dolnego Bugu). Some localities are in the Wołomin Plain (Równina Wołomińska) and the Siedlce Plateau (Wysoczyzna Siedlecka). The analysed species occur in various natural and semi-natural habitats, such as xerothermic and sandy grasslands, floodplain meadows, wetlands, bogs, and forests. Data were collected during field research carried out in 2021-2023. In the left-bank part of the Lower Bug Valley, 45 species of protected plants were recorded, but also red-listed or regionally rare plants (90 species in total). They include 16 species are under strict protection, 29 under partial protection, and 35 species are rare in the region. Some of the localities described earlier by other authors were found again or verified. In the Lower Bug Valley, there are almost all plant associations known from Mazovia, including the extremely valuable boreal Sphagno girgensohnii-Piceetum, protected in the “Jegiel” reserve. There are also oak forests on the edge of the Siedlce Plateau. The valleys of the Bug and its tributaries are dominated by areas of cultivation, arable fields, meadows, and forests. Some species considered to be common in other regions are rare in the Bug river valley, e.g. Hepatica nobilis, Asarum europaeum, Isopyrum thalictroides. This is because their habitats are sparse or degraded. However, some other species, rare in other regions, are common in the study area, e.g. Allium angulosum, Euphorbia lucida, and Hierochloë odorata on floodplain meadows, Salvinia natans in oxbow lakes, and Arctostaphylos uva-ursi in pine forests and sandy grasslands. The only locality of Blechnum spicant in this part of Mazovia was found in this study. The species is characteristic of montane forests and fir-spruce forests. Two localities of Diphasiastrum tristachyum were recorded, in typical habitats of this species: heaths formed after forest fires.